The Double-Edged Effects of Dual-Identity on the Emotional Exhaustion of Migrant Workers: An Existential Approach - Li, Xiaobei; Zhang, Hongyu; Zhang, Jianjun (Frontiers in Psychology, 2020)
By integrating an existential approach to burnout, identity theory, and the job demand–resource (JD–R) model, this paper compares the sense-making processes of migrant workers who embrace both rural and urban identities (i.e., dual-identity holders) with those who suppress either identity (i.e., non-dual-identity holders). In particular, we have examined these dual-identity holders’ interpretations of the workplace regarding internal corporate social responsibilities (CSR) efforts and job complexity and the subsequent emotional exhaustion. A sample of 1,985 migrant workers in China reveals that dual-identity holders may have decreased emotional exhaustion because of higher perceptions of internal CSR efforts, and increased emotional exhaustion because of higher perceptions of job complexity. Furthermore, it is found that human resource management (HRM) strength (i.e., employees’ shared perceptions of HR practices) weakens those two relationships. These findings have important implications for managing migrant workers and ensuring their well-beings.